(untitled) (Research, Society and Development, 2022)
Antibiotics are drugs that are intended to kill bacteria or inhibit their growth. They present a great advance in the history of medicine, but the inadequate use and little knowledge of people contribute to a major public health problem, bacterial resistance. In this way, this research was proposed with the objective of understanding the knowledge of the students of the 9th year of a public school in the city of Manaus - Amazonas about this problem and verifying the knowledge about the microorganisms. Data were collected through the application of a questionnaire to 32 students. According to the results, it was verified that the students do not have an adequate knowledge about these concepts and, even if correct, they presented incomplete and superficial answers. Therefore, this topic needs to be further developed in the classroom, which contributes to satisfactory learning, in order to obtain more meaningful learning and the development of critical and scientific thinking. The authors reform that studies that promote education and health should be approached in an interdisciplinary way, for a broad and meaningful understanding in the daily lives of students.